2011
DOI: 10.3390/en4030545
|View full text |Cite
|
Sign up to set email alerts
|

Application of the NOx Reaction Model for Development of Low-NOx Combustion Technology for Pulverized Coals by Using the Gas Phase Stoichiometric Ratio Index

Abstract: Abstract:We previously proposed the gas phase stoichiometric ratio (SRgas) as an index to evaluate NO x concentration in fuel-rich flames. The SRgas index was defined as the amount of fuel required for stoichiometric combustion/amount of gasified fuel, where the amount of gasified fuel was the amount of fuel which had been released to the gas phase by pyrolysis, oxidation and gasification reactions. In the present study we found that SRgas was a good index to consider the gas phase reaction mechanism in fuel-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Particulate matter (PM) with an aerodynamic diameter of less than 10 µm (PM 10 ) is a vital pollutant produced in the process of coal utilization. For meeting the increasingly stringent emission standards, the formation mechanism and control method of PM 10 during coal combustion have always been the focus of research [1][2][3][4]. In the target of the ultra-low emission of pollutants from coal-fired boilers, the emission limit of PM 10 is less than 5 mg/m 3 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter (PM) with an aerodynamic diameter of less than 10 µm (PM 10 ) is a vital pollutant produced in the process of coal utilization. For meeting the increasingly stringent emission standards, the formation mechanism and control method of PM 10 during coal combustion have always been the focus of research [1][2][3][4]. In the target of the ultra-low emission of pollutants from coal-fired boilers, the emission limit of PM 10 is less than 5 mg/m 3 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of intermediate species, such as HCN, NH 3 , and hydrocarbons have been measured previously. 5,6 Then, fourth, we also examined concentrations of H 2 S, which is an important intermediate species that causes corrosion 7 of the water wall of boilers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several studies have examined the relationships between the stoichiometric ratio and product concentration. 5,6,8 For numerical calculations, databases representing relationships between stoichiometric ratio and species concentrations have usually been used in order to shorten the calculation time. 9,10 We proposed the index of gas-phase stoichiometric ratio (SRgas), in order to examine the NOx reaction for pulverized coal combustion.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, currently more and more scholars have turned to studying solid fuel reburning and have found that it is more promising than gas reburning in denitration [8][9][10][11][12][13][14]. In the combustion process, mechanisms of the formation and reduction of NOx are extremely crucial and have been studied extensively [15][16][17][18][19]. Julien Cances [20] conducted experiments and modelling with four major solid fuels to identify the difference in the contributions of volatile matters and char to the NOx reduction, and found that for a short initial residence time, volatiles contribute more to the NOx reduction than char, and that after the short initial residence time, char contributes more.…”
Section: Introductionmentioning
confidence: 99%